2012
DOI: 10.1111/tbed.12002
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Mediated Immune Response During Experimental Acute Infection with Bovine Viral Diarrhoea Virus: Evaluation of Blood Parameters

Abstract: Acute infections with bovine viral diarrhoea virus (BVDV), a major pathogen of cattle, are often asymptomatic or produce only mild clinical symptoms. However, they may play an important role in the bovine respiratory disease complex by exerting a marked immunosuppressive effect, as a result of the death of the immunocompetent cell populations involved in controlling innate and adaptive immune responses, together with a marked reduction of both cytokine expression and co-stimulatory molecule synthesis. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 86 publications
3
15
2
Order By: Relevance
“…As infection-induced changes in circulating concentrations of these specific cytokines can occur earlier than 4 d postinoculation (reviewed by Kelling and Topliff, 2013), changes may have been missed due to the sampling schedule followed in the current study. Results from a recent study (Molina et al, 2012) demonstrated earlier increases in serum TNF-α, IFN-γ, and IL-12 and an associated decrease in IL-1β in older calves (8 to 9 . Treatment means that differed on a specific day are indicated by *P < 0.10 (strong trend), **P < 0.05, ***P < 0.01, and ****P < 0.001.…”
Section: Serum Cytokine Concentrationsmentioning
confidence: 93%
“…As infection-induced changes in circulating concentrations of these specific cytokines can occur earlier than 4 d postinoculation (reviewed by Kelling and Topliff, 2013), changes may have been missed due to the sampling schedule followed in the current study. Results from a recent study (Molina et al, 2012) demonstrated earlier increases in serum TNF-α, IFN-γ, and IL-12 and an associated decrease in IL-1β in older calves (8 to 9 . Treatment means that differed on a specific day are indicated by *P < 0.10 (strong trend), **P < 0.05, ***P < 0.01, and ****P < 0.001.…”
Section: Serum Cytokine Concentrationsmentioning
confidence: 93%
“…The disease state induced can range from acute, subclinical infections of immunocompetent cattle to persistent infection that can lead to mucosal disease, which is usually fatal due to superinfection of persistently infected animals with antigenically homologous cp virus or de novo generation of a cp variant of the persisting ncp virus (3). BVDV has been shown to infect cells pivotal in control of both the innate and adaptive immune responses (4), and infection has been shown to be immunosuppressive (5,6). Transient immunosuppression occurs in acutely infected animals (7), permitting colonization and replication by opportunistic pathogens (8,9).…”
mentioning
confidence: 99%
“…A previous study by our group focused on the first 12 dpi with BVDV revealed a transitory decrease in monocytes (Molina et al., ). After these 12 days of infection with BVDV, circulating monocytes were restored to normal values and maintained with no significant changes after BHV‐1 inoculation (Molina et al., ), coinciding with systemic results from other authors (Falkenberg et al., ).…”
Section: Discussionmentioning
confidence: 71%
“…Hence, to maintain a stable population, there must be an influx of new T cells replacing those that are decaying (Stromberg and Antia, ). In this study, we observed an increase in CD8+ T cells in the thymus medulla of BVDV‐infected calves that might take place as a result of a compensatory mechanism of cytotoxic T lymphocyte (CTL) mobilization in response to the intense CD8 systemic depletion observed in the coinfected animals during the acute phase of BVD (Molina et al., ), which was maintained after BHV‐1 inoculation (Molina et al., ).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation